Meningkatkan Hasil Belajar Siswa Melalui Metode Card Short dalam Pembelajaran PAI di SD Negeri 10 Rambah Lanai - Efendi, Yulfan (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ learning outcomes in the subject of Islamic Religious Education (PAI) by using the Card Sort learning method at SD Negeri 10 Rambah Lanai. The research was conducted in two cycles, with each cycle involving stages of planning, implementation, observation, and reflection. The results showed that in Cycle I, the students’ completion rate was 65%, while in Cycle II, it increased to 90%. This indicates a significant improvement in students’ learning outcomes after the implementation of the Card Sort method. Furthermore, both student and teacher activities showed good improvement. In conclusion, the Card Sort method can enhance students’ learning outcomes in the subject of PAI at SD Negeri 10 Rambah Lanai.